A monitoring and warning system for expressway slopes using FBG sensing technology. (May 2018) - Hu, Yongqiang; Hong, Chengyu; Zhang, Yifan; Li, Guowei
This article presents a fiber Bragg grating–based monitoring and warning system for expressway slopes. A detailed architecture of the sensing system based on fiber Bragg grating sensors for safety analysis and pre-warning of slopes is described and interpreted. The whole warning and monitoring system was mainly realized based on two monitored parameters from fiber Bragg grating strain sensors: (1) the measured bend strain of inclinometers for the calculation of horizontal displacement and (2) axial strain distributions of soil nails. The maximum magnitudes of cumulative strain and displacement in the present monitored expressway slope were 198 με and 5.06 mm, respectively. Critical threshold values of different warning levels for expressway slopes have been proposed using statistical analysis method based on comparative analysis of history monitored data from slopes in the same region. A total of four warning levels characterized by different ranges of displacement rates and the related engineering measures to treat expressway slopes were proposed and discussed. This fiber Bragg grating–based monitoring system of soil nails and inclinometers forms a real-time sensing network, assisting engineers to adopt quick and essential measures to deal with potential landslide risk.